ANALYSIS OF THE PRODUCTION PROCESS AT PT TBA.ALAM SUTERA USING THE VALUE STREAM MAPPING METHOD - Haryadi Sarjono; Stevin Dewa Yusuf; Gilang Ananta Ferrial (Bina Nusantara University, 2020)
Each Production Process must have a shortage that may not have very short-term effects but in the long run waste can disrupt the effectiveness of the resources in the company. Minimizing waste in the production process is one of the goals of a company. Value stream mapping is one of the lean methods that can minimize waste in the production process. In this study, the method used to reduce production time at PT. TBA.is a fishbone and Value Stream Mapping (VSM). VSM is used to see the condition of production time in the company. To look for waste in the use of fishbone and to reduce it using line balancing. Found 2 line balancing that is unnecessary motion and unnecessary inventory. With this method we know the total cycle time of 69.06 minutes and the company can reduce 43.4% or 30 minutes of lead time from the total cycle time.